P11.19.B Bevacizumab in recurrent WHO grade 2-3 gliomas. (5th September 2022) - Annakib, S; Rigau, V; Darlix, A; Gozé, C; Duffau, H; Bauchet, L; Mollevi, C; Fabbro, M
Abstract: Background: Medical management of recurrent WHO grade 2-3 (rGII/III) gliomas is not well established. Bevacizumab (BEV) is an option at malignant recurrence. Yet, very few data are available in this indication. The aim of this study is to describe clinical outcomes in patients treated with BEV. Material and Methods: A retrospective study was conducted including patients treated by BEV for a rGII/III glioma at our institution (2011 - 2019). Data were collected from medical records. Tumor samples were reviewed according to the WHO 2016 classification. Efficacy was assessed according RANO criteria. Progression Free Survival (PFS) and Overall Survival (OS) from BEV initiation were estimated using the Kaplan-Meier method. A Cox proportional hazards model was performed to estimate Hazard Ratios with 95% Confident Intervals (CI). Results: A total of 81 patients was included (sex ratio: 1.6 M/W, median age at diagnosis: 38). Among them, 46 patients (56.8%) had a grade 2 and 35 (43.2%) a grade 3 glioma. The histological forms were astrocytoma (grade 2 -3) IDH mutated in 27 patients (33.3%), IDHwt in 15 patients (18.5%) and oligodendroglioma (grade 2 - 3) in 13 patients (16%). Twenty-six patients were not reclassified. Previous treatment included tumor resection for all patients (second intervention in 22.2%). First-line medical treatment consisted of chemotherapy in 60.5% patients before any radiotherapy. Chemotherapy was rechallenged in 52 patients (64.2%). All patients but one received radiation therapy and 19 patients (23.5%) received a reirradiation. BEV was administered at 10 or 15mg/kilogram every 2 or 3 weeks. All patients had a contrast enhancement on MRI at baseline. Median number of BEV cycles was 7 [1-79], in association with chemotherapy in 45.7%. Partial response, stable disease and progressive disease was observed in 27.2%, 22.2% and 50.6% respectively. Median OS from BEV introduction was 7.6 months (95% CI [5.5;9.9]). Median PFS was 4.9 months (95% CI [3.7;6.1]). In univariate analysis, grade 2 (Odd Ratio (OR)=0.41, 95% CI [0.17;1.02], p=0.054), Ki67<7% (OR=0.41, 95% CI [0.15;1.21], p=0.079) and initial total surgical resection (OR=2.75, 95% CI [0.68;11.11], p=0.097) showed a trend for delayed progression. BEV was stopped for progression in 70.4%, for toxicity in 8.6% and for others reasons in 21% patients. Twenty-four patients (29.6%) discontinued BEV without progression (medical decision, BEV toxicity or patient decision). Presence of 1p19q codeletion (OR=0.24, 95% CI [0.07;0.84], p=0.023) and age ≥ 38 (OR=0.36, 95% CI [0.13;0.99], p=0.042) at diagnosis were more frequent in this sub-population. Out these of 24 patients, 8 showed survival from 3 months to 5 years without any other treatment. Conclusion: BEV can be a good option for patients with rGII/III glioma. One third of them stopped treatment without progression, reaching a survival of several years for some of them.